GENETIC DIVERSITY FOR HEAT TOLERANCE TRAITS IN SPRING WHEAT (Triticum aestivum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2012)
The present investigation was undertaken with the objective to identify the extent of genetic diversity for traits related to heat tolerance among 25 currently available spring wheat genotypes under late sowing condition during the cropping season 2009-2010. All genotypes were distributed into five clusters showing considerable genetic divergence for most of the heat tolerant traits under study. The role of grain filling rate and biomass production in both the vectors had the highest contribution to genetic divergence. The positive values of both the vectors for flag leaf senescence, ground coverage, spikes number, 1000-grain weight, grain yield (g m-2) and harvest index indicating high contribution of these traits towards the divergence among 25 genotypes of wheat. Three pair of clusters, viz. I & II, I & III and I & V can be considered for obtaining more heterotic progeny as the genetic distance between these clusters were larger. Considering yield performances, cluster distance and cluster mean the genotype G-22 from cluster I and genotype G-14 from cluster IV may be considered better parents for further breeding of heat tolerance as they showed maximum divergence and high degree of tolerance to heat under late sowing condition. Moreover, the genotype G-22 could be exploited for direct release as a heat tolerant variety after testing under wider range of environments.DOI: http://dx.doi.org/10.3329/bjpbg.v25i2.18663